Democracia com liderança: Max Weber e o conceito de democracia plebiscitária - Sell, Carlos Eduardo (Revista Brasileira de Ciência Política, 2012)
Resumo As complexas relações entre regimes políticos (burocracia) e liderança política (carisma) ocupam o centro da reflexão sociopolítica de Max Weber. Este artigo propõe-se a examinar esta temática a partir do conceito weberiano de democracia plebiscitária. O trabalho está dividido em quatro partes. A primeira examina a trajetória do conceito nos escritos políticos e sociológicos de Weber. Após reconstruir a biografia do conceito, o segundo tópico analisa o tema do ponto de vista sistemático. Distinguem-se, então, três tipos sociológicos de democracia na teoria weberiana: democracia direta, democracia parlamentar e democracia plebiscitária. A terceira seção dedica-se a apresentar o tema sob um enfoque normativo, destacando as motivações que levaram Max Weber a defender o reforço do potencial cesarista das modernas democracias de massa. A parte final é dedicada ao balanço geral do trabalho. Palavras-chave: Max Weber; democracia; democracia parlamentar; democracia plebiscitária. Abstract The complex relationships between political regimes (bureaucracy) and political leaderships (charisma) is central to the socio-political thinking of Max Weber. This article aims at examining this issue from the perspective of the Weberian concept of plebiscitary democracy. The work is divided into four parts. The first examines the trajectory of the concept in Weber’s political and sociological writings. After a reconstruction the biography of the concept, the second topic examines the issue from a systematic point of view. Three sociological types of democracy are, then, distinguished in the Weberian theory: direct democracy, parliamentary democracy and plebiscitary democracy. The third section is dedicated to present the issue under a normative approach, highlighting the motivations that led Max Weber to argue in favor of the enhancement of the Caesarist potential of modern mass democracies. The final part is dedicated to an overall account of the work. Key words: Max Weber; democracy; parliamentary democracy; plebiscitary democracy.